Systematic literature review: Determinants and contribution of restaurant tax to local own-source revenue in Indonesia - Karyanto, Karyanto; Sofyani, Hafiez (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This research aims to explore previous research related to the contribution of restaurant taxes in Indonesia to Local Own-Source Revenue (LOSR) and analyze studies from several angles.Design/Methodology/Approach: This research used a Systematic Literature Review, which consisted of three stages, namely the collection stage, by entering the search keywords